Virtual organization as a queuing system - Пальонна, Тетяна Анатоліївна (Technology audit and production reserves, 2012)
The article describes such subspecies of virtual organization as a virtual laboratory. We propose mathematical models of virtual organization functioning on the basis of the queuing theory. The efficiency characteristics are considered